Financial Inclusion and Carbon Reduction: Evidence From Chinese Counties - Yang, Zhenkai; Yu, Lu; Liu, Yinwei; Yin, Zhichao; Xiao, Zumian (Frontiers in Environmental Science, 2022)
This paper investigates whether financial inclusion contributes to the carbon reduction in China using county-level dataset. A fixed-effect panel regression approach is adopted to examine the impact of financial inclusion on county-level regional carbon emissions. The estimation results imply that financial inclusion plays an important role in reducing carbon emissions. The mediation effect analysis reveals two channels through which financial inclusion imposes negative impact on the level of regional carbon emissions. One is to elevate the carbon sequestration capacity by increasing vegetation coverage, and the other is to improve the industrial structure through enhanced financial support. In addition to being a bridge between economic opportunity and output, financial inclusion can also act as an effective measure for addressing climate change.